Private encroachment through crisis-making: The privatization of education for refugees - Le, Hang Minh (Education Policy Analysis Archives, 2019)
How has education for refugees been shaped by broader dynamics of educational privatization? This paper argues that the invoking of the ‘refugee crisis’ narrative has been a crucial force in facilitating the privatization of this sector. The urgency of crisis helps to naturalize private actors’ participation in refugees’ education as equal partners to host governments, multilateral agencies, and civil society. Consistent with Stephen Ball’s (2012) distinction between privatization in and of education, the privatization of refugee education also advances through two dimensions: the creation of a new space – a new ‘market’ – for private actors, and the infusion of market and business principles such as ‘innovation’ into all aspects of education. The crisis narrative has created a new ‘horizon of taken-for-granted’ (Hall, 1993), where it is simply natural that private actors must participate in the assumption of the traditional responsibilities of the state in providing education for refugees.